2021
DOI: 10.1007/s13197-021-05038-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blanching and pickling process on the alcohol acyltransferase (AAT) activity, myristicin content and quality parameters of pickled nutmeg (Myristica fragrans)

Abstract: Myristicin, a potential toxicant, is a major ester present in the pericarp of nutmeg (Myristica fragrans) and alcohol acyltransferase (AAT) is responsible for its generation. The objective of the study was firstly to estimate the effect of blanching and pickling process on the inactivation of AAT and production of myristicin in nutmeg pericarp. Secondly, the effect of pickling process on the physical, microbial, antioxidant and sensory properties of nutmeg was evaluated. The nutmeg fruit pericarp was water-bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…Further, we compared our results with literature data on crude plant material to reveal that the spent material is an important source of bioactive compounds. In a study by Rahman et al [30], the total phenolic content in four nutmeg seed samples ranged from 0.174 to 1.891 mg GAE/100 g. Sulaiman and Ooi [31] documented a lower total phenolic content (46.3 mg GAE/g) in an 80% methanol extract of nutmeg seeds as compared to the value reported in our study. Pashapoor et al [32] reported total phenolic and flavonoid levels in the petroleum ether of nutmeg seeds of 112.41 mg GAE/100g dry weight (DW) and 26.12 mg quercetin equivalents (QE)/100 g DW, respectively.…”
Section: Total Phenolic and Flavonoid Contentscontrasting
confidence: 67%
“…Further, we compared our results with literature data on crude plant material to reveal that the spent material is an important source of bioactive compounds. In a study by Rahman et al [30], the total phenolic content in four nutmeg seed samples ranged from 0.174 to 1.891 mg GAE/100 g. Sulaiman and Ooi [31] documented a lower total phenolic content (46.3 mg GAE/g) in an 80% methanol extract of nutmeg seeds as compared to the value reported in our study. Pashapoor et al [32] reported total phenolic and flavonoid levels in the petroleum ether of nutmeg seeds of 112.41 mg GAE/100g dry weight (DW) and 26.12 mg quercetin equivalents (QE)/100 g DW, respectively.…”
Section: Total Phenolic and Flavonoid Contentscontrasting
confidence: 67%
“…Also, it was noticed that, adding garlic to the RR and BR affected the pickle hardness, where it was found that, the hardness of RRG and BRG treatments were significantly lower than the RRC and BRC treatments all over the 60 days. Rahman et al (2022) observed more than 50% reduction in hardness of blanched nutmeg pickle whereas the time of the blanching time increase the hardness decrease and reported that this may be happened due to the tissue softening under high temperature. Badwaik et al (2016) reported that, the turgor pressure increases within the cell structure during the blanching treatments which forces the cell membrane against the cell wall and cause a loss in fruit texture.…”
Section: Hardness Of Red Beetroot Pickle Treatmentsmentioning
confidence: 96%
“…During the production of fermented vegetables, some operating units, such as blanching, affect the activity of alcohol acyltransferase (AAT) and would influence the content of myristicin and other quality parameters in nutmeg [ 75 ]. The fermentation conditions indirectly affect the nutrient changes in fermented vegetables.…”
Section: The Dynamic Process Of the Fermentation Of Pickled Vegetablesmentioning
confidence: 99%